Dangerous waters : an adventure on Titanic - Mone, Gregory (Square Fish, 2013)
Determined to focus on work rather than books, as his father had, twelve-year-old Patrick Waters leaves Belfast as a steward on the Titanic, but the very wealthy Harry Widener arranges to tutor him, drawing Patrick into association with thieves seeking Harry's very rare edition of Francis Bacon's Essays.